2022
DOI: 10.23863/kalem.2021.199
|View full text |Cite
|
Sign up to set email alerts
|

Kovid-19 Salgını Sürecinde Özel Gereksinimli Çocukları Olan Ebeveynlerin İhtiyaçları

Abstract: olgu bilim (fenomenoloji) deseni ile yürütülmüştür. Çalışmanın katılımcıları, kolay ulaşılır durum örneklemesi yöntemi ile ilin öğrenci sayısı açısından en yoğun olduğu bir özel eğitim ve rehabilitasyon merkezine çocukları devam eden 273 ebeveyndir. Katılımcıların %30'u bedensel yetersizliği, % 25'i zihin yetersizliği ve %16'sı otizm spektrum bozukluğu olan çocukların ebeveynleridir. Elde edilen veriler araştırma soruları ve betimsel analiz ile değerlendirilmiştir. Ebeveynlerin ihtiyaçlarının eğitim, sosyal ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In this process, the stress and anxiety that family members experienced due to restrictions may have also adversely affected these children (Öpengin, 2020). Yıldırım‐Parlak et al (2022) indicated that parents experienced anxiety because their children stayed away from education. Likewise, studies examining the life patterns of children and their families during this pandemic period found that families experienced health anxiety about being protected from the pandemic, on the one hand and yet also had to manage problem behaviors because of the change in their children's routines (Colizzi et al, 2020; Narzisi, 2020).…”
mentioning
confidence: 99%
“…In this process, the stress and anxiety that family members experienced due to restrictions may have also adversely affected these children (Öpengin, 2020). Yıldırım‐Parlak et al (2022) indicated that parents experienced anxiety because their children stayed away from education. Likewise, studies examining the life patterns of children and their families during this pandemic period found that families experienced health anxiety about being protected from the pandemic, on the one hand and yet also had to manage problem behaviors because of the change in their children's routines (Colizzi et al, 2020; Narzisi, 2020).…”
mentioning
confidence: 99%